Evaluation of thermodynamic data for aqueous Ca-U(VI)-CO3 species under conditions characteristic of geological clay formation. (January 2021) - Maia, Flávia M.S.; Ribet, Solange; Bailly, Céline; Grivé, Mireia; Madé, Benoît; Montavon, Gilles
Abstract: Uranium(VI) forms stable Ca-U(VI)-CO3 ternary complexes, which are highly mobile in the environment. This characteristic can be critical as regards radioactive waste disposal in deep geological formations. While the formation of aqueous ternary Ca-U(VI)-CO3 complexes has been clearly established and identified under room temperature conditions, the effect of temperature on their formation has barely been investigated. An experimental study was thus designed to evaluate the stability of these complexes with temperature (20–80 °C) under well-controlled physicochemical conditions typical of clay rock formation (especially CO2 pressure). This method is based on a study of the competition between the processes of complex formation and uranium retention on an anion-exchange resin. A modelling approach with PhreeqC code, using the Davies equation for the calculation of the activity coefficients, was carried out to derive the thermodynamic data for the formation of these complexes. The Van't Hoff Equation can be applied to explain the variation in stability constant values as a function of temperature. This work suggests: log10 β 113 o = 27.27 ± 0.04 and log10 β 213 o = 29.8 ± 0.2 for CaUO2 (CO3 )3 2- and Ca2 UO2 (CO3 )3 (aq) complexes, respectively, hence in good agreement with the literature data. The enthalpy of reaction determined here from experiments suggests that temperature does not facilitate the formation of CaUO2 (CO3 )3 2- ( Δ r H m o  = −24.4 ± 2.2 kJ mol −1 ), whereas it has very little effect on the stability of Ca2 UO2 (CO3 )3 (aq) ( Δ r H m o  = −3 ± 10 kJ mol −1 ). Highlights: A set-up was designed in order to work in a biphasic solid/liquid system by means of controlling the temperature and  p CO2 . The Van't Hoff Equation is used to describe the variation in stability constant values as a function of temperature (20-80°C). The temperature does not favour the formation of CaUO2 (CO3 )3 2-, whereas it has little effect on Ca2 UO2 (CO3 )3 (aq).